From fecal microbiota transplantation toward next-generation beneficial microbes: The case of Anaerobutyricum soehngenii - Wortelboer, Koen; Koopen, Annefleur M.; Herrema, Hilde; de Vos, Willem M.; Nieuwdorp, Max; Kemper, E. Marleen (Frontiers in Medicine, 2022)
The commensal gut microbiota is important for human health and well-being whereas deviations of the gut microbiota have been associated with a multitude of diseases. Restoration of a balanced and diverse microbiota by fecal microbiota transplantation (FMT) has emerged as a potential treatment strategy and promising tool to study causality of the microbiota in disease pathogenesis. However, FMT comes with logistical challenges and potential safety risks, such as the transfer of pathogenic microorganisms, undesired phenotypes or an increased risk of developing disease later in life. Therefore, a more controlled, personalized mixture of cultured beneficial microbes might prove a better alternative. Most of these beneficial microbes will be endogenous commensals to the host without a long history of safe and beneficial use and are therefore commonly referred to as next-generation probiotics (NGP) or live biotherapeutic products (LBP). Following a previous FMT study within our group, the commensal butyrate producer Anaerobutyricum spp. (previously named Eubacterium hallii) was found to be associated with improved insulin-sensitivity in subjects with the metabolic syndrome. After the preclinical testing with A. soehngenii in mice models was completed, the strain was produced under controlled conditions and several clinical studies evaluating its safety and efficacy in humans were performed. Here, we describe and reflect on the development of A. soehngenii for clinical use, providing practical guidance for the development and testing of NGPs and reflecting on the current regulatory framework.